Measuring Smart City Implementation to Improve the Quality of Public Services in Jambi City - cahyadi kurniawan; Irfandi Pratama; Titin Purnawingsih; Ulung Pribadi (International Journal of Artificial Intelligence Research, 2022)
The city of Jambi is part of the movement towards 100 smart cities in 2017, along with Bandung and Sleman. The purpose of this study is to measure the implementation of smart cities to improve service quality in Jambi City by using a two-dimensional smart city approach, namely; smart government and smart living. Furthermore, the research method used in this study is a qualitative approach with the help of Nvivo 12 Plus softwear. The type of data in this study uses primary and secondary data obtained from social media, online media, and journal literature. The results of the study explain that access to public information disclosure can still not be said to be transparent, it is also strengthened that the rules regarding smart city councils still do not exist. Explaining and reaffirming the 2018-2023 RPJMD in chapter IV Jambi City faces problems and challenges in implementing smart cities and e-government, with the main problems not yet optimal implementation of the Electronic-Based Government System (SPBE), and smart city supporting regulations . It is a record of the government how to optimize all innovations that have been implemented, some applications do not run smoothly, and even are not active which are only made to meet needs without considering sustainability. Smart city comes hand in hand with the principle of Sustainability development It is a record of the government how to optimize all innovations that have been implemented, some applications do not run smoothly, and even are not active which are only made to meet needs without considering sustainability. Smart city comes hand in hand with the principle of Sustainability development It is a record of the government how to optimize all innovations that have been implemented, some applications do not run smoothly, and even are not active which are only made to meet needs without considering sustainability. Smart city comes hand in hand with the principle of Sustainability development